Regional epigenetic variation in asexual snail populations among urban and rural lakes. Issue 4 (7th November 2019) - Thorson, Jennifer L M; Smithson, Mark; Sadler-Riggleman, Ingrid; Beck, Daniel; Dybdahl, Mark; Skinner, Michael K
Abstract: Epigenetic variation has the potential to influence environmentally dependent development and contribute to phenotypic responses to local environments. Environmental epigenetic studies of sexual organisms confirm the capacity to respond through epigenetic variation. An epigenetic response could be even more important in a population when genetic variation is lacking. A previous study of an asexual snail, Potamopyrgus antipodarum, demonstrated that different populations derived from a single clonal lineage differed in both shell phenotype and methylation signature when comparing lake versus river populations. Here, we examine methylation variation among lakes that differ in environmental disturbance and pollution histories. Snails were collected from a more pristine rural Lake 1 (Lake Lytle), and two urban lakes, Lake 2 (Capitol Lake) and Lake 3 (Lake Washington) on the Northwest Pacific coast. DNA methylation was assessed for each sample population using methylated DNA immunoprecipitation, MeDIP, followed by next-generation sequencing. The differential DNA methylation regions (DMRs) identified among the different lake comparisons suggested a higher number of DMRs and variation between rural Lake 1 and one urban Lake 2, and between the two urban Lakes 2 and 3, but limited variation between the rural Lake 1 and urban Lake 3. DMR genomic characteristics and gene associations were investigated. The presence of site-specific differences between each of these lake populations suggest an epigenetic response to varied environmental factors. The results do not support an effect of geographic distance in these populations. The role of dispersal distance among lakes, population history, environmental pollution and stably inherited methylation versus environmentally triggered methylation in producing the observed epigenetic variation are discussed. Observations support the proposal that epigenetic alterations may associate with phenotypic variation and environmental factors and history of the different lakes.